PRODUCT INNOVATION: MAINTAINING COMPETITIVENESS IN A COMPETITIVE MARKET - Dewi Indriani Jusuf (Jurnal Ekonomi, 2022)
Today's global market is characterized by increasingly fierce competition, with rapid changes in consumer preferences and technological advances. The aim of this research is to analyze how product innovation can be a key strategy for companies to remain relevant and superior in a changing market. This research uses a qualitative approach with descriptive methods. The research results show that product innovation has been proven to have a significant positive impact on the company's business growth and success. By continuing to develop innovative products that are responsive to market needs and consumer preferences, companies can increase revenue and profits, strengthen their brand image, and expand their market share. Product innovation also plays a crucial role in maintaining a company's competitiveness in a competitive market, by helping companies identify new opportunities, create product distinctiveness, and strengthen relationships with customers. Through a planned and integrated approach to product innovation, companies can remain major players in an ever-changing and dynamic industry.